Surgical management of delayed Gartland type III supracondylar humeral fractures in children: A retrospective comparison of radial external fixator and crossed pinning. Issue 10 (March 2020) - Li, Jin; Rai, Saroj; Tang, Xin; Ze, Renhao; Liu, Ruikang; Hong, Pan
Abstract : Abstract: Radial external fixator has been proposed to treat delayed irreducible Gartland type III supracondylar humeral fracture, and this study aims to compare its effects with crossed pinning in a retrospective fashion. Delayed supracondylar humeral fracture is defined as more than 72 hours after injury, 2 or more than 2 times failed attempts of closed reduction can be deemed as irreducible fracture. Between January 2010 and January 2017, patients of Gartland type III supracondylar fractures of the humerus receiving surgery were all selected and reviewed. Overall, 39 patients fitting the inclusion criteria were chosen for the External Fixator Group and patients for control group of crossed pinning with matched age, sex, and clinical parameters (fracture location, injured side, and fracture type) were selected from the database. Surgery duration, number of intraoperative X-ray images, incidence of ulnar nerve injury, postoperative redisplacement, and function of the elbow joint were recorded and analyzed. In this study, 39 patients treated with radial external fixator had significantly shorter surgery duration, fewer intraoperative X-ray images, and lower incidence of ulnar nerve injury, and postoperative redisplacement than those receiving crossed pinning. Patients in 2 groups displayed similar range of motion for elbow joint at follow-up. Radial external fixator is an effective and safe method to treat Gartland type III supracondylar fractures that were diagnosed late.